Enhancing physical activity levels in 9–11-year-old children of varied genders: strategies leveraging parental exercise consciousness - Song, Chao; Ge, Sha (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to explore the predictive associations of parental exercise consciousness with the physical activity (PA) status and characteristics of 9–11-year-old children, in an attempt to identify effective strategies for addressing PA insufficiency in children from a parental standpoint.MethodsThe PA rating scale-3 and the Chinese Civic Exercise Consciousness Questionnaire were used to measure primary school students’ PA and their parents’ exercise consciousness from 361 families in Tianjin, China. The dimensions of exercise consciousness were cognition and identity (CI), sentiment and intention (SI), attitude and willingness (AW), and rights and responsibilities (RR) dimensions. Descriptive statistics, ANOVA with post-hoc test analysis, correlation analysis, and hierarchical regression analysis were performed.ResultsFirst, children’s PA increased with age, with boys significantly exceeding girls (p < 0.01). Significant gender differences were observed in both PA intensity and frequency (boys higher than girls, p < 0.01), although this was not consistent across age groups. Variations in PA duration and frequency showed significant age-related changes (p < 0.01), whereas intensity showed significant changes at older ages (p < 0.01). Second, we observed moderate to above-average level of parental exercise consciousness, and a significantly positive correlation between parental exercise consciousness and children’s PA levels (α = 0.601, p < 0.01); meanwhile, all four dimensions of parental exercise consciousness showed varying degrees of positive correlations with children’s PA intensity, duration, and frequency (p < 0.01). Third, stratified linear regression analysis showed the varied predictive associations of the different dimensions of parental exercise consciousness with children’s PA intensity, duration, and frequency. SI and AW significantly predictively associated with PA levels across different age groups and genders (p < 0.05).ConclusionAge and gender showed crucial associations with children’s PA levels, resulting in distinct preferences and behaviors between boys and girls across various age groups. Parental exercise consciousness of exercise positively associated with the intensity, frequency, and overall volume of children’s PA. Enhancing parental consciousness of exercise-related emotions, intentions, attitudes, and willingness may effectively associate with enhancements in the intensity, duration, and frequency of their children’s PA, ultimately promoting greater engagement in physical exercise among the youth.